INFLUENCE OF PUBLIC PROCUREMENT AND ASSET DISPOSAL ACT, 2015 ON PERFORMANCE OF COUNTY GOVERNMENTS IN KENYA - Ngoima, Rose Kavithe; Ndeto, Charles (International Journal of Supply Chain and Logistics, 2022)
Purpose: The study purpose was to examine influence of public procurement and asset disposal Act (PPADA, 2015) on performance of county governments in Kenya with an aim of making recommendations on proper use. Methodology: The study employed a descriptive research design. The study was confined to seven (7) county governments in Kenya which have a budget allocation of above Ksh 10 Billion according to FY 2019/2020 budgetary allocation by the National Treasury. Data collection was from procurement officers at the various county headquarters specifically from senior to the middle levels of management. The researcher preferred this method because it allowed an in-depth study of the subject. Data was collected using self-administered questionnaires. Structured questionnaires were used to collect data. Data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 22 Results and conclusion: The findings of the study indicated that regulatory agencies, procurement methods, reservations and preferences and assets disposal have a positive relationship with performance of county governments in Kenya.The findings of the study indicated that regulatory agencies, procurement methods, reservations and preferences and assets disposal have a positive relationship with performance of county governments in Kenya Policy recommendation: the study recommended that public institutions should embrace regulatory agencies, procurement methods, reservations and preferences and assets disposal so as to improve performance of county governments and further researches should to be carried out in other public institutions to find out if the same results can be obtained